A novel intermediate host for Taenia serialis (Gervais, 1847): The European roe deer (Capreolus capreolus L. 1758) from the Monti Sibillini National Park (MSNP), Italy. (April 2022) - Morandi, Benedetto; Bazzucchi, Alessandra; Gambini, Sofia; Crotti, Silvia; Cruciani, Deborah; Morandi, Federico; Napoleoni, Maira; Piseddu, Toni; Di Donato, Alessandra; Gavaudan, Stefano
Abstract: Taeniids are multi-host parasites with an indirect life cycle that strictly depends on a predator-prey relationship. Parasites with a complex life cycle may exhibit different degrees of host-specificity at each life stage. Knowing the host breadth is a fundamental concept of the biology and epidemiology of these multi-host parasites. Morphological identification of tapeworms is challenging and occasionally may produce misdiagnosis. Thus, molecular investigations were carried out for the identification of parasitic cysts detected from muscle tissues in a male roe deer necropsied at the Istituto Zooprofilattico Sperimentale dell'Umbria e delle Marche "Togo Rosati" (Central Italy). Sanger sequencing showed 99% query cover, 2e-109 e-value, and 100% identity with Taenia serialis . The exact definitive host was not revealed in this report, but red foxes and Italian wolves may play a significant role as being widespread within the area. Wildlife surveillance is crucial to monitor for human and animal health since global distribution and flexibility in intermediate hosts of many and even more critical taeniids species may enlarge their host range. Graphical abstract: Image 1 Highlights: A new intermediate host for a not commonly detected tapeworm was documented. A new ecological niche might be hypothesized. Molecular investigation is crucial for the diagnosis of tapeworms to avoid misdiagnosis. To perform necropsy on wildlife is essential for the local and global understanding of free-living animal populations.